Faktor Penghambat Pemberian ASI Ekslusif Pada Ibu Penderita - Muhammad Syukri; Nurbaya Nurbaya; Icha Dian Nurcahyani; Ikrimah Nafilata; Monika Eskadela (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The coverage of exclusive breastfeeding in the working area of the Hiang Health Center is still low. Family support and support from health workers such as midwives are very influential in the breastfeeding practice. Therefore, this study aimed to examine the relationship between family support and support from health workers in exclusive breastfeeding. This research was an analytical observation with a cross-sectional approach which was carried out in the working area of the Hiang Health Center, Kerinci Regency, Jambi in April-May 2021. Data processing was carried out with univariate and bivariate analysis using the chi-square test. The results showed that lack of family support, especially in-laws was 4,07 times at risk (95% CI: 1,81-9,12) and lack of support from health workers was 3,46 times at risk (95% CI: 1,50-7,96). These two factors were inhibiting factors in exclusive breastfeeding. Health workers need to improve breastfeeding education and counseling services and involve husbands and in-laws in these activities so that they will support mothers in the practice of exclusive breastfeeding.